Reasoning Texts. Ritorico-stylistical aspects (the example of English) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
Ritorico-stylistical aspects of reasoning texts composition being analyzed and delineated their main text-forming parameters. Text typology problem on the level of speech composition being investigated, taking into account lingvo-stylistical factors.
Keywords: reasoning texts; composition; logic-structural peculiarities; topology; essay